PC / PMMA / ABS composite material and preparation method and application thereof
By adding transesterification accelerator and compatibilizer to PC/PMMA/ABS composites, the amount of resin is optimized, and the existing materials have been solved, and the problems of low scratch resistance and color pearlescent marking are achieved, achieving high tensile strength and impact resistance Sex and good appearance, suitable for car interiors.
Patent Information
- Application Number
- CN202411543837.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
Smart Images

Figure BDA0005113342110000031 
Figure BDA0005113342110000101 
Figure BDA0005113342110000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a PC / PMMA / ABS composite material and a preparation method and application thereof. Background Art
[0002] Traditional automotive interior parts are produced by spray painting for aesthetic effect. However, it is difficult to recycle plastic products after spray painting, which will affect reuse. In addition, the spray painting process is cumbersome, costly, pollutes the environment, has a high scrap rate, and produces toxic and harmful gases, which seriously endangers human health. Therefore, the use of spray-free materials is becoming more and more widespread. PC / ABS (polycarbonate / acrylonitrile-styrene-butadiene copolymer) composite material is a common engineering plastic alloy. Due to its high heat resistance and excellent mechanical properties, it is widely used in automotive interiors. Since automotive interior parts are often touched or bumped, major OEMs have higher and higher requirements for the scratch resistance of automotive interior materials.
[0003] At present, there are many studies and reports on scratch-resistant PC / ABS materials. For example, CN109825054A discloses a PC / ABS alloy with scratch resistance and its preparation method, the alloy includes the following components by weight: PC: 30-80, ABS: 15-60, polyvinylidene fluoride masterbatch: 1-20, compatibilizer: 0.5-5, toughening agent 2-15, antioxidant 0.1-1, lubricant 0.1-1; prepare the materials according to the above components and weight parts, then put the above materials except polyvinylidene fluoride masterbatch into a medium-speed mixer, mix for 5-30 minutes, obtain a mixed material, finally put the mixed material into a twin-screw extruder, control the screw speed to 180-600rpm, feed the polyvinylidene fluoride masterbatch from the side, melt-extrusion, granulation, and obtain a product with excellent scratch resistance. For another example, CN105623233A discloses a wear-resistant and scratch-resistant injection-molding grade PC / ABS alloy material, which is composed of the following components by weight: 35-75% PC, 15-60% ABS, 2-5% compounded compatibilizer, 1-3% compounded toughening agent, 1-3% lubricant, 0.5-1% antioxidant, and 0.5-1% anti-ultraviolet agent; the compounded compatibilizer is an interface compatibilizer compounded of polyolefin elastomer POE and modified polyolefin, and the compounding ratio is 1:1-1:3, wherein the modified polyolefin is maleic anhydride grafted polypropylene (PP-g-MAH), and the grafting rate is 3-5%; the compounded toughening agent is a compound of thermoplastic rubber, polyolefin and modified nano-calcium carbonate; the invention greatly improves the compatibility of the PC and ABS interface by adopting the compounded compatibilizer. However, the compatibilizers used in the above two inventions are improperly selected, which results in the resulting PC / ABS alloy having relatively low scratch resistance and the surface is still very easily scratched.
[0004] Polymethyl methacrylate (PMMA) is a high molecular polymer, also known as acrylic or plexiglass, which has the advantages of high transparency, high hardness, high weather resistance and scratch resistance. Combining PC resin, ABS resin and PMMA resin to make a ternary alloy can effectively improve the scratch resistance of PC / ABS alloy. For example, CN105348724A discloses a high-gloss, high-hardness, scratch-resistant modified PC / ABS alloy material and a preparation method thereof. The alloy material contains the following raw material components by weight percentage: PC content is 10-30%, ABS content is 30-70%, PMMA content is 10-30%, compatibilizer content is 1-10%, toughening agent is 1-10%, anti-scratch modifier content is 1-10%, coupling agent is 0.1-1%, antioxidant content is 0.1-1%, and processing aid content is 0.1-1%; the preparation method comprises placing the aforementioned components in a high-speed mixer in turn and mixing at high speed for 3-5 minutes, and sending them into a screw extruder for extrusion granulation. The product prepared by this method has comparable mechanical properties and higher heat resistance to PC / ABS. However, the compatibility between PC resin and PMMA resin is not very good, which will seriously affect the mechanical properties and scratch resistance of the final product. If the usage ratio of the two cannot be well controlled, colorful pearlescent patterns will easily appear on the product surface, seriously affecting its application in automotive interiors.
[0005] Therefore, there is an urgent need to develop a PC / PMMA / ABS composite material with excellent mechanical properties, scratch resistance and good appearance. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a PC / PMMA / ABS composite material and a preparation method and application thereof. The components in the PC / PMMA / ABS composite material have good compatibility, and thus can have high tensile strength, excellent impact resistance and excellent scratch resistance, and the appearance does not have the phenomenon of colorful pearlescent patterns, and is suitable for application in automobile interiors.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a PC / PMMA / ABS composite material, wherein the PC / PMMA / ABS composite material comprises the following components in parts by weight:
[0009]
[0010] The PC / PMMA / ABS composite material provided by the present invention comprises PC resin, PMMA resin, ABS resin, a compatibilizer, an ester exchange accelerator and other additives; by selecting three resin matrices of PC resin, PMMA resin and ABS resin and matching them within a specific dosage range, in particular, adding PMMA resin, the scratch resistance of the composite material is effectively improved; at the same time, the compatibilizer and the ester exchange accelerator are added for modification, and the two are synergistically compounded, which can effectively improve the compatibility of the above three resins; in particular, the addition of the ester exchange accelerator can make the PC resin and the PMMA resin undergo an ester exchange reaction in a specific ratio, thereby greatly improving the compatibility of the two, and thereby making the obtained PC / PMMA / ABS composite material have excellent scratch resistance on the premise of having excellent impact resistance and high tensile strength, and no colorful pearlescent pattern phenomenon will appear on the appearance, and is very suitable for preparing automobile interiors.
[0011] Among them, the amount of the PC resin can be 50 parts by weight, 52 parts by weight, 54 parts by weight, 56 parts by weight, 58 parts by weight, 60 parts by weight, 62 parts by weight, 64 parts by weight or 65 parts by weight, and the mass proportion of the PC resin in the PC / PMMA / ABS composite material is ≥45%.
[0012] The PMMA resin may be used in an amount of 5 parts by weight, 7 parts by weight, 9 parts by weight, 11 parts by weight, 13 parts by weight, 15 parts by weight, 17 parts by weight, 19 parts by weight or 20 parts by weight.
[0013] The amount of the ABS resin can be 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight or 25 parts by weight.
[0014] The amount of the compatibilizer can be 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.6 parts by weight, 2.8 parts by weight, 3 parts by weight, 3.2 parts by weight, 3.4 parts by weight or 3.6 parts by weight, etc.
[0015] The amount of the transesterification promoter can be 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight or 0.5 parts by weight, etc.
[0016] The amount of the other auxiliary agents can be 0 parts by weight, 3 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight or 20 parts by weight, etc.
[0017] Preferably, the melt index of the PC resin is 2 to 65 g / 10 min, for example, 2 g / 10 min, 3 g / 10 min, 5 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 18 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 55 g / 10 min or 60 g / 10 min, and more preferably 6 to 50 g / 10 min. The test temperature is 300 ° C and the load is 1.2 kg.
[0018] Preferably, the PC resin includes bisphenol A polycarbonate.
[0019] Preferably, the melt index of the PMMA resin is 1 to 20 g / 10 min, for example, 1 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, 9 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, 18 g / 10 min or 20 g / 10 min, the test temperature is 230 ° C, and the load is 3.8 kg.
[0020] Preferably, the melt index of the ABS resin is 10 to 20 g / 10 min, for example, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, 18 g / 10 min or 20 g / 10 min, etc., the test temperature is 220° C., and the load is 10 kg.
[0021] In the present invention, the melt index of the PC resin, ABS resin and PMMA resin can be tested according to the method provided in ISO 1133-1:2022 standard.
[0022] Preferably, the average particle size of the rubber phase in the ABS resin is 300-700 nm, for example, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm or 700 nm.
[0023] Preferably, the content of the compatibilizer in the PC / PMMA / ABS composite material is 2.5 to 2.8 parts by weight, for example, 2.5 parts by weight, 2.55 parts by weight, 2.6 parts by weight, 2.65 parts by weight, 2.7 parts by weight, 2.75 parts by weight or 2.8 parts by weight, etc.; in the present invention, the compatibilizer is further limited to the above-mentioned dosage range, which can optimize the compatibility of the PC resin, PMMA resin and ABS resin, thereby ensuring that the mechanical properties, scratch resistance and appearance of the final PC / PMMA / ABS composite material are optimized.
[0024] Preferably, the compatibilizer comprises a styrene-acrylate copolymer.
[0025] Preferably, the content of the transesterification accelerator in the PC / PMMA / ABS composite material is 0.08 to 0.2 parts by weight, for example, 0.08 parts by weight, 0.085 parts by weight, 0.09 parts by weight, 0.095 parts by weight, 0.1 parts by weight, 0.12 parts by weight, 0.14 parts by weight, 0.16 parts by weight, 0.18 parts by weight or 0.2 parts by weight, etc.; in the present invention, the transesterification accelerator is further limited to the above range, so that the PC resin and the PMMA resin can achieve optimal compatibility, thereby ensuring that the obtained PC / PMMA / ABS composite material has optimal mechanical properties, scratch resistance and appearance.
[0026] Preferably, the transesterification accelerator includes any one of diphenyl carbonate, polymethacryloyl azomethine or acrylate oligomer, or a combination of at least two thereof.
[0027] Preferably, the other additives include any one or a combination of at least two of a toughening agent, an antioxidant, a lubricant, a silicone masterbatch, a light stabilizer or a color masterbatch.
[0028] Preferably, the content of the toughening agent in the PC / PMMA / ABS composite material is 3 to 6 parts by weight, for example, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight, 5 parts by weight or 5.5 parts by weight.
[0029] Preferably, the toughening agent comprises an acrylate silicone copolymer.
[0030] Preferably, the content of antioxidant in the PC / PMMA / ABS composite material is 0.2 to 1 part by weight, for example, 0.2 part by weight, 0.3 part by weight, 0.4 part by weight, 0.5 part by weight, 0.6 part by weight, 0.7 part by weight, 0.8 part by weight, 0.9 part by weight or 1 part by weight.
[0031] Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a thioester antioxidant, a phosphite antioxidant or a hindered amine antioxidant, or a combination of at least two thereof.
[0032] Preferably, the content of lubricant in the PC / PMMA / ABS composite material is 0.2 to 1 part by weight, for example, 0.2 part by weight, 0.3 part by weight, 0.4 part by weight, 0.5 part by weight, 0.6 part by weight, 0.7 part by weight, 0.8 part by weight, 0.9 part by weight or 1 part by weight.
[0033] Preferably, the lubricant includes any one or a combination of at least two of silane polymer, magnesium stearate, pentaerythritol stearate, butyl stearate, stearic acid, fatty acid salt, fatty acid amide, ethylene bisstearamide or polyethylene wax.
[0034] Preferably, the content of light stabilizer in the PC / PMMA / ABS composite material is 1 to 3 parts by weight, for example, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.6 parts by weight, 2.8 parts by weight or 3 parts by weight, etc.
[0035] Preferably, the light stabilizer includes a hindered amine light stabilizer and / or a benzotriazole light stabilizer.
[0036] Preferably, the content of silicone masterbatch in the PC / PMMA / ABS composite material is 0.5 to 4 parts by weight, for example, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight or 4 parts by weight.
[0037] In the present invention, there is no special requirement for the type of the silicone masterbatch, and conventional products in the art may be selected. For example, a silicone masterbatch having a carrier of MBS / SBS and an active ingredient of ultra-high molecular weight polysiloxane may be selected.
[0038] Preferably, the content of masterbatch in the PC / PMMA / ABS composite material is 2 to 3 parts by weight, for example, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.6 parts by weight, 2.8 parts by weight or 3 parts by weight.
[0039] In the present invention, there is no special requirement for the color of the masterbatch, and the color can be selected according to the requirements of the final product. Similarly, there is no special requirement for the type of the masterbatch of a specific color selected, and a conventional commercially available masterbatch product of the specific color can be selected; for example, if the color of the required masterbatch is black, a black masterbatch obtained by blending a styrene-acrylonitrile copolymer and carbon black can be selected.
[0040] In a second aspect, the present invention provides a method for preparing the PC / PMMA / ABS composite material as described in the first aspect, the preparation method comprising: putting PC resin, PMMA resin, ABS resin, a compatibilizer, an ester exchange promoter and other additives into a twin-screw extruder, and obtaining the PC / PMMA / ABS composite material through melt extrusion, cooling and drying.
[0041] Preferably, the twin-screw extruder is a co-rotating twin-screw extruder.
[0042] Preferably, the screw aspect ratio of the twin-screw extruder is 25 to 48 (e.g., 25, 30, 35, 40, 45 or 48, etc.), the screw barrel vacuum is -0.08 to -0.1 MPa (e.g., -0.08 MPa, -0.082 MPa, -0.084 MPa, -0.086 MPa, -0.088 MPa, -0.09 MPa, -0.092 MPa, -0.094 MPa, -0.096 MPa, -0.098 MPa or -0.1 MPa, etc.), and the temperature of the screw feed conveying section is 200 to 220°C (e.g., 200°C, 202°C, 204°C, 206°C, 208°C, 210°C , 212°C, 214°C, 216°C, 218°C or 220°C, etc.), the temperature of the core plasticizing section is 250-260°C (for example, 250°C, 252°C, 254°C, 256°C, 258°C or 260°C, etc.), the temperature of the post-homogenizing extrusion section is 250-260°C (for example, 250°C, 252°C, 254°C, 256°C, 258°C or 260°C, etc.), and the screw speed is 400-600rpm (for example, 400rpm, 420rpm, 440rpm, 460rpm, 480rpm, 500rpm, 520rpm, 540rpm, 560rpm, 580rpm or 600rpm, etc.).
[0043] In a third aspect, the present invention provides a use of the PC / PMMA / ABS composite material as described in the first aspect in preparing automotive interior parts.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The PC / PMMA / ABS composite material provided by the present invention comprises PC resin, PMMA resin, ABS resin, a compatibilizer, an ester exchange accelerator and other additives. By selecting the three resins of PC resin, PMMA resin and ABS resin to be matched within a specific dosage range, and adding the compatibilizer and the ester exchange accelerator to assist, the three resins have good compatibility, thereby ensuring that the final PC / PMMA / ABS composite material has both excellent mechanical properties and scratch resistance, and does not have a fantasy pearlescent pattern phenomenon in appearance, and is very suitable for automotive interiors. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0047] Unless otherwise specified, the materials involved in the following examples and comparative examples are conventional materials in the art and can be purchased commercially; in particular, the information of some raw materials involved is as follows:
[0048] (1) PC resin
[0049] PC-1: melt index is 20g / 10min (300℃ / 1.2kg), purchased from Idemitsu Kosan Co., Ltd., Japan, brand FN1900;
[0050] PC-2: melt index is 10g / 10min (300℃ / 1.2kg), purchased from Mitsubishi, Japan, brand S-2000F;
[0051] PC-3: melt index is 3g / 10min (300℃ / 1.2kg), purchased from Samyang, South Korea, brand name TRIREX3030PJ;
[0052] PC-4: melt index is 60 g / 10 min (300°C / 1.2 kg), purchased from Wanhua Chemical, brand name PC2600.
[0053] (2) ABS resin: melt index is 15 g / 10 min (220° C. / 10 kg), purchased from Sinopec Shanghai Gaoqiao Petrochemical Co., Ltd., brand ABS 8434.
[0054] (3) PMMA resin
[0055] PMMA-1: melt index is 3 g / 10 min (230°C / 3.8 kg), purchased from Rohm Chemical (Shanghai) Co., Ltd., brand 8N;
[0056] PMMA-2: melt index is 2g / 10min (230℃ / 3.8kg), purchased from Mitsubishi Rayon, brand number VH 001;
[0057] PMMA-3: melt index is 17 g / 10 min (230° C. / 3.8 kg), purchased from Taiwan Chi Mei, brand CM-211.
[0058] (4) Compatibilizer: styrene-acrylate copolymer, purchased from Jiayirong Polymer (Shanghai) Co., Ltd., brand name HPC-3128.
[0059] (5) Transesterification accelerator
[0060] Diphenyl carbonate: commonly available on the market, and each embodiment and comparative example uses the same commercially available product;
[0061] Polymethacryloyl azomethine: commonly available on the market, and each embodiment and comparative example uses the same commercially available product;
[0062] Acrylate oligomer: commonly available on the market, and each example and comparative example uses the same commercially available product.
[0063] (6) Toughening agent: acrylic ester silicone copolymer, purchased from Mitsubishi Rayon Polymer Materials (Nantong) Co., Ltd., brand S-2001.
[0064] (7) Antioxidants
[0065] Antioxidant 1010: hindered phenol antioxidant, purchased from BASF SE;
[0066] Antioxidant 168: phosphite antioxidant, purchased from BASF AG.
[0067] (8) Lubricant
[0068] Pentaerythritol stearate: purchased from Italy Faji, brand name PETS-AP;
[0069] Ethylene bisstearamide: purchased from KLK, Malaysia, brand name EBS-SF.
[0070] (9) Silicone masterbatch: The carrier is MBS / SBS, the weight percentage of the active ingredient polysiloxane is 50%, purchased from Dongguan PolyGao Chemical, brand SI-S50.
[0071] (10) Light stabilizer
[0072] Hindered amine light stabilizer-1: purchased from BASF AG, brand name TINUVIN 770DF;
[0073] Hindered amine light stabilizer-2: purchased from BASF SE, brand name CHIMASSORB 944FDL;
[0074] Benzotriazole light stabilizer: purchased from BASF AG, brand name TINUVIN 234.
[0075] (12) Black masterbatch: The base resin is SAN resin, and the additive is carbon black. The mass percentage of carbon black is 50%, purchased from ECOS of South Korea, with the brand number CB5093.
[0076] (13) ASA resin: purchased from Donghai Plastics, brand name Q800.
[0077] Examples 1 to 14 and Comparative Examples 1 to 8
[0078] Examples 1 to 14 respectively provide a PC / PMMA / ABS composite material, and the components and amounts thereof are shown in Table 1 and Table 2;
[0079] In Table 1 and Table 2, the dosage units of each component are all "parts by weight":
[0080] Table 1
[0081]
[0082]
[0083] Table 2
[0084]
[0085] Comparative Examples 1 to 8 provide a composite material, respectively, and the components and amounts thereof are shown in Table 3; in Table 3, the amount units of each component are "parts by weight":
[0086] Table 3
[0087]
[0088] The preparation methods of the PC / PMMA / ABS composite materials provided in Examples 1 to 14 and Comparative Examples 1 to 8 include the following steps:
[0089] The pre-dried PC resin, PMMA resin, ABS resin, toughening agent, compatibilizer, transesterification accelerator, antioxidant, lubricant, silicone masterbatch, light stabilizer and black seed were mixed according to the composition formula in Tables 1 to 3 and added into the main barrel of the twin-screw extruder. The temperature of each section of the main barrel (from the feed port to the die outlet) was controlled to 200° C., 220° C., 240° C., 250° C., 260° C., 255° C. and 260° C., respectively. The twin-screw speed was 500 rpm. The molten extruded material strips were cooled, dried and pelletized to obtain the PC / PMMA / ABS composite material.
[0090] Performance Testing:
[0091] (1) Tensile strength: tested in accordance with ISO 527-2012 standard, with a tensile rate of 50 mm / min.
[0092] (2) Charpy notched impact strength: tested in accordance with ISO 179-1:2010, injection molding A-notch.
[0093] (3) Scratch resistance: The composite material is injection molded into a sample and tested according to the test method provided by Volkswagen PV3991. The brightness change value (△L) is recorded. The smaller the brightness change value, the better the scratch resistance.
[0094] (4) Appearance evaluation: The composite material was continuously injection molded into 20 square plates of 100×100×3 mm using a high-gloss mold. Ten of them were randomly selected and placed on D 65 Visually observe under the light source at a visual distance of about 20cm to check whether there is any defective appearance such as iridescent pearlescent pattern on the surface of the square plate, and record the number of square plates with iridescent pearlescent pattern, and then classify them according to the following standards:
[0095] If no iridescent pearlescent pattern appears on the surface of any of the 10 square plates, the appearance grade is 1;
[0096] If only one of the 10 square plates has iridescent pearlescent patterns, the appearance grade is 2;
[0097] If 2 to 3 square plates among 10 square plates have colorful pearlescent patterns, the appearance grade is 3;
[0098] If 4 to 5 square plates among 10 square plates have iridescent pearlescent patterns, the appearance grade is 4;
[0099] If more than 5 of the 10 square plates have iridescent pearlescent patterns, the appearance grade is 5.
[0100] The composite materials provided in Examples 1 to 14 and Comparative Examples 1 to 8 were tested according to the above test method. The test results are shown in Table 4:
[0101] Table 4
[0102]
[0103]
[0104] From the data in Table 4, we can see that:
[0105] (1) The PC / PMMA / ABS composite materials provided in Examples 1 to 14 have a tensile strength of 50 to 54 MPa and a simply supported beam notched impact strength of 38 to 48 kJ / m 2 , the scratch resistance test △L is 0.5~0.85, and the appearance evaluation can reach level 1~2, with high tensile strength, excellent impact resistance, scratch resistance and good appearance;
[0106] By further optimizing the amount of each component and further limiting the melt index of the PC resin, the PC / PMMA / ABS composite materials obtained in Examples 1 to 8 have a tensile strength of 52 to 54 MPa and a simply supported beam notched impact strength of 43 to 48 kJ / m 2 The scratch resistance test △L is 0.5~0.65, the appearance evaluation can reach level 1, and the comprehensive performance has reached the best.
[0107] (2) Compared with Example 1, the composite materials provided in Comparative Examples 1 to 8 cannot have high tensile strength, excellent impact resistance, scratch resistance and good appearance. The specific analysis is as follows:
[0108] First, in Comparative Example 1, PMMA resin was not added, and the scratch resistance was poor. In Comparative Example 2, ABS resin was not added, and the impact resistance and appearance were both poor. In Comparative Example 3, PC resin was not added, and the impact resistance was poor and the tensile strength was low. This shows that only by using PC resin, PMMA resin and ABS resin as three matrices can a composite material with high tensile strength, excellent impact resistance, scratch resistance and good appearance be obtained, and none of the three is indispensable.
[0109] Secondly, by comparing the data of Example 1 and Comparative Examples 4 to 6, it can be seen that too low an amount of compatibilizer (Comparative Example 4), too much an amount of compatibilizer (Comparative Example 5), and no addition of an ester exchange accelerator (Comparative Example 6) will all lead to a decrease in the compatibility of the three matrices of PC resin, PMMA resin, and ABS resin in the obtained composite material, and thus the tensile strength, impact resistance, scratch resistance, and overall appearance of the composite material cannot be taken into account at the same time;
[0110] Furthermore, by comparing the data of Example 1 and Comparative Example 7, it can be seen that in the absence of a compatibilizer (Comparative Example 7), even if the amount of ester exchange promoter is increased, the compatibility of the three matrices of PC resin, PMMA resin and ABS resin in the obtained composite material will decrease, thereby causing a significant decrease in the tensile strength, impact resistance, scratch resistance and overall appearance of the composite material.
[0111] Finally, by comparing the data of Example 1 and Comparative Example 8, it can be seen that using ASA resin to replace ABS resin will lead to a decrease in both the tensile strength and the scratch resistance of the obtained composite material, especially the scratch resistance is very poor.
[0112] In summary, for the PC / PMMA / ABS composite material provided by the present invention, the ratio of PC resin, PMMA resin and ABS resin is very important, and the addition and dosage of compatibilizer and ester exchange promoter are also very important. By reasonably controlling the addition amount of compatibilizer and ester exchange promoter, the compatibilizer of the obtained PC / ABS / PMMA composite material is better, and then a PC / PMMA / ABS composite material with good appearance, excellent impact resistance, high tensile strength and excellent friction resistance can be obtained.
[0113] The applicant declares that the present invention illustrates a PC / PMMA / ABS composite material and its preparation method and application through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A PC / PMMA / ABS composite material, characterized in that: The PC / PMMA / ABS composite material comprises the following components in parts by weight:
2. The PC / PMMA / ABS composite material according to claim 1, wherein the PC resin has a melt index of 2 to 65 g / 10 min, preferably 6 to 50 g / 10 min, when tested at 300°C and 1.2 kg. Preferably, the melt index of the PMMA resin tested at 230° C. and 3.8 kg is 1 to 20 g / 10 min; Preferably, the melt index of the ABS resin tested at 220° C. and 10 kg is 10 to 20 g / 10 min.
3. The PC / PMMA / ABS composite material according to claim 1 or 2, characterized in that: The content of the compatibilizer in the PC / PMMA / ABS composite material is 2 to 2.8 parts by weight; Preferably, the compatibilizer comprises a styrene-acrylate copolymer.
4. The PC / PMMA / ABS composite material according to claim 1 or 3, characterized in that: The content of the transesterification accelerator in the PC / PMMA / ABS composite material is 0.08 to 0.2 parts by weight; Preferably, the transesterification accelerator includes any one of diphenyl carbonate, polymethacryloyl azomethine or acrylate oligomer, or a combination of at least two thereof.
5. The PC / PMMA / ABS composite material according to claim 1 or 2, characterized in that: The other additives include any one or a combination of at least two of a toughening agent, an antioxidant, a lubricant, a silicone masterbatch, a light stabilizer or a color masterbatch; Preferably, the content of toughening agent in the PC / PMMA / ABS composite material is 3 to 6 parts by weight; Preferably, the toughening agent comprises an acrylate silicone copolymer; Preferably, the content of antioxidant in the PC / PMMA / ABS composite material is 0.2 to 1 parts by weight; Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a thioester antioxidant, a phosphite antioxidant or a hindered amine antioxidant, or a combination of at least two thereof.
6. The PC / PMMA / ABS composite material according to claim 5, characterized in that: The content of lubricant in the PC / PMMA / ABS composite material is 0.2 to 1 parts by weight; Preferably, the lubricant includes any one or a combination of at least two of silane polymer, magnesium stearate, pentaerythritol stearate, butyl stearate, stearic acid, fatty acid salt, fatty acid amide, ethylene bisstearamide or polyethylene wax.
7. The PC / PMMA / ABS composite material according to claim 5 or 6, characterized in that: The content of the light stabilizer in the PC / PMMA / ABS composite material is 1 to 3 parts by weight; Preferably, the light stabilizer comprises a hindered amine light stabilizer and / or a benzotriazole light stabilizer; Preferably, the content of silicone masterbatch in the PC / PMMA / ABS composite material is 0.5 to 4 parts by weight; Preferably, the content of masterbatch in the PC / PMMA / ABS composite material is 2 to 3 parts by weight.
8. A method for preparing the PC / PMMA / ABS composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: putting PC resin, PMMA resin, ABS resin, compatibilizer, ester exchange accelerator and other additives into a twin-screw extruder, and obtaining the PC / PMMA / ABS composite material through melt extrusion, cooling and drying.
9. The preparation method according to claim 8, characterized in that: The twin-screw extruder is a twin-screw extruder rotating in the same direction; Preferably, the screw aspect ratio of the twin-screw extruder is 25 to 48, the screw barrel vacuum is -0.08 to -0.1 MPa, the screw feeding and conveying section temperature is 200 to 220°C, the core plasticizing section temperature is 250 to 260°C, the post-homogenizing extrusion section temperature is 250 to 260°C, and the screw speed is 400 to 600 rpm.
10. Use of the PC / PMMA / ABS composite material according to any one of claims 1 to 7 in the preparation of automotive interior parts.
Citation Information
Cited By
Low-phase-difference PMMA optical film and preparation method thereof
CN120040898A
A low phase difference PMMA optical film and a method for manufacturing the same
CN120040898B
